2011
DOI: 10.1002/lsm.21036
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy outcome for oral dysplasia

Abstract: 5-ALA-PDT and/or mTHPC-PDT offer an effective alternative treatment for oral potentially malignant disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
94
2
2

Year Published

2015
2015
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 11 publications
1
94
2
2
Order By: Relevance
“…Two studies [19,20] reported the frequency of smoking. In the study by Jerjes et al [20], 49 individuals smoked less than 20 daily and 38 patients smoked more than 20 cigarettes per day. In the study by Pietruska et al [19], all smokers (n = 6) smoked less than 10 cigarettes daily.…”
Section: General Characteristics Of the Studiesmentioning
confidence: 98%
See 3 more Smart Citations
“…Two studies [19,20] reported the frequency of smoking. In the study by Jerjes et al [20], 49 individuals smoked less than 20 daily and 38 patients smoked more than 20 cigarettes per day. In the study by Pietruska et al [19], all smokers (n = 6) smoked less than 10 cigarettes daily.…”
Section: General Characteristics Of the Studiesmentioning
confidence: 98%
“…In 9 studies [15][16][17][18][19][20][22][23][24], smokers (ranging between 5 and 87 individuals) were included. Two studies [19,20] reported the frequency of smoking.…”
Section: General Characteristics Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Trabalhos clínicos recentes têm demonstrado que a PDT pode se constituir uma alternativa viável para o tratamento de CEC bucal. A PDT mediada pelo 5-ALA tem sido usado no tratamento de lesões potencialmente malignas (Chen et al, 2005;Tsai et al, 2004) e CEC bucal pouco invasivos Fan et al, 1996) com resultados clínicos promissores (Biel, 2007;Jerjes et al, 2011a). Quando comparada às terapias convencionais (cirurgia, radio e quimioterapia), a PDT tem como vantagem o fato de ser uma técnica minimamente invasiva, que leva à destruição do tumor com preservação do tecido sadio.…”
Section: Terapia Fotodinâmica E Cec Bucalunclassified